A Comparative Study of News Framing of COVID-19 Crisis Management in South Korea and China - Yue Jin; Seongku Hong; Hyunju Kang (Journalism and Media)
This study examines how major newspapers in South Korea and China portrayed national crisis management during the COVID-19 pandemic. Utilizing a mixed-methods approach that combines quantitative content analysis with qualitative interpretation, this study systematically analyzes news frames and editorial tones across various phases. The qualitative analysis further clarifies the quantitative results. Editorials from The Chosun Daily, Hankyoreh, People’s Daily, and Ming Pao covering the period from 1 January 2020, to 31 March 2023, were reviewed. The research categorizes the pandemic into three distinct phases: the global spread of COVID-19, vaccine rollout, and living with the virus. It applies three news frames: crisis response, international relations, and responsibility attribution. In the initial phase, most newspapers focused on the crisis response frame, highlighting national mobilization and social solidarity. Notably, The Chosun Daily emphasized the international relations frame with the strongest critical tone. The crisis response frame continued to dominate in the second phase, accompanied by an increasingly critical tone. In the final phase, as the pandemic began to stabilize, the international relations frame significantly declined due to fewer global differences in pandemic responses. The results suggest that the media’s portrayal is influenced by political orientation and approaches to crisis management perspectives.